TINDAKAN MELAWAN HUKUM ANALISIS TERHADAP BENTUK DAN EFEKTIVITAS REGULASI DALAM MENCEGAH ANCAMAN KESELAMATAN ANGKUTAN UDARA - Sujono; Rahmat, Diding; Zein Sgn, Subhan (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2025)
Illegal acts in aviation are a serious threat to air transport safety, which can have a broad impact on the global transportation system. This study aims to identify forms of illegal acts that can endanger aviation safety and analyze the effectiveness of existing legal regulations in dealing with them. The method used is normative legal research with a statutory approach and a conceptual approach. The results of the study indicate that forms of illegal acts that can endanger aviation safety include aircraft hijacking, smuggling of illegal goods, sabotage of aircraft or aviation infrastructure, negligence or violation of flight procedures, terrorism, use of drones for illegal purposes, and violations of passenger and cargo security. Existing legal regulations, such as the 1963 Tokyo Convention, the 1970 Hague Convention, the 1971 Montreal Convention, and Law No. 15 of 2003 concerning Criminal Acts of Terrorism, provide a strong legal basis in dealing with these threats. However, its effectiveness still requires improvement through consistent law enforcement, increasing the capacity of related institutions, and adapting to the development of new threats in the aviation sector.